Pemberdayaan Masyarakat Sadar Hipertensi Melalui Pelatihan Terapi Pijat Kaki Rendam Kaki dan Senam Hipertensi pada Kelompok Penderita Hipertensi Desa Lubuk Batang - Lisdahayati; Pome, Gunardi; Marwan, Marwan; Saprianto, Saprianto; Martadinata, Umar Hasan; Rustiati, Nelly; Aisyah, Aisyah (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Hypertension remains a significant public health concern, particularly in developing countries such as Indonesia, due to its asymptomatic nature and potential for severe complications. Objective: This community engagement activity aimed to empower hypertensive patients in Lubuk Batang Baru Village through training in complementary therapies including foot massage, foot soaking, and hypertension exercises to improve knowledge and self-care practices. Method: This participatory program was conducted from July to October 2023 across four sessions. Participants included patients with hypertension, their families, health cadres, village midwives, and nursing students. Activities comprised pre-tests, education sessions using visual media, hands-on demonstrations of complementary therapies, and post-intervention evaluations. Follow-up home visits were conducted to assess the implementation of self-care practices. Result: The intervention significantly improved participants’ knowledge and skills. The percentage of participants with good knowledge increased from 23.3% to 83.3% after four months. Many participants reported regularly practicing foot massage and foot soaking at home, leading to better sleep and reduced muscle cramps. The use of demonstration methods, educational materials, and active family involvement played a critical role in the success of the program. Conclusion: Community empowerment through structured education and practical training in complementary hypertension therapies effectively enhances knowledge, behavior, and self-management among hypertensive patients.